When I Fall in Love with Machine: Cultural Identity of the Taiwanese in the Era of New Technology with Regard to the Works of Huang Yi Studio - Gryszkiewicz, Anna (Porównania, 2022)
This article could be read as a multi-voice, dynamic and being-in-progress model of relations that connect (could be linked to) a choreographic clip of the Taiwanese dance group Huang Yi Studio +, the establishment of a new Daimler AG factory in Sindelfingen and a sudden acceleration of work on Comprehensive Agreement on Investment between China and the EU at the end of 2020. Considering all of these events, I ask the question: What is the cultural identity of Taiwanese in the era of post-media, cyber-physical industrial culture and technological wars, and what role does artistic activity play in its production.